Telemedicine (Online Medical Services) Dalam Era New Normal Ditinjau Berdasarkan Hukum Kesehatan (Studi: Program Telemedicine Indonesia/Temenin Di Rumah Sakit Dr. Cipto Mangunkusumo) - Andrianto, Wahyu; Athira, Amira Budi (UI Scholars Hub, 2022)
Health is an important basis for the continuity of human life. Every human being has the right to have access to safe, quality, and affordable health services. However, in reality health services in Indonesia still have several obstacles, for examples the lack of health care for remote areas which is hindered by distance and time. Especially during the Corona Virus Disease 2019 (COVID-19) pandemic, a solution is needed to serve public health without violating the regulations that enforce Large-Scale Social Restrictions (PSBB) to prevent the spread of the virus. For this reason, one of the efforts that can be carried out is by “making friends” or utilizing information technology, namely in the form of Telemedicine. Telemedicine is the provision of remote medical services using information and communication technology, which will facilitate access to health services for the public. The purpose of this study was to analyze the application of Telemedicine services in the New Normal Era, especially in the Indonesian Telemedicine Program (TEMENIN) by the Ministry of Health of the Republic of Indonesia at Dr. Cipto Mangunkusumo Hospital. The research method used is normative juridical. The results of the study state that the implementation of Telemedicine services during the New Normal Era mostly refers to the regulations and policies of the Ministry of Health, and is supported by the existence of various Telemedicine applications. However, it does not yet have an official platform from the Government that can guarantee storage and data confidentiality. The author concludes that Telemedicine which already has many benefits, still has several obstacles in it. Furthermore, the author suggests that the Government immediately create a special platform for Telemedicine services, accompanied by laws and regulations or special regulations, which are supported by government agencies or authorities that can oversee its implementation prevent malpractice.